(untitled) (Bangladesh Journal of Medical Science, 2025)
Background This study analyzes the effect of self-efficacy on perceived stress among experimental science teachers in public high schools in the city of Tetouan, Morocco. Methods We used two instruments in this cross-sectional study to measure perceived stress and self-efficacy rates among 258 participating teachers. The Perceived Stress Scale (PSS-10) assessed stress levels, while the Teacher Sense of Self-Efficacy Scale (TSES) measured selfefficacy across three dimensions: teaching strategies, student engagement, and classroom management. Results There is a significant correlation between teachers’ perceived stress and the three dimensions of the TSES. Age, years of teaching experience, number of classes taught, and regular physical activity were all significant indicators of reported stress. We found that weekly working hours and physical activity negatively influenced the level of self-efficacy. Conclusion These findings emphasize the pivotal significance of self-efficacy in diminishing stress and alleviating its detrimental consequences. Hence, it is imperative to prioritize the improvement of teachers’ psychological well-being. Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 433-439